GAMBARAN HASIL STATUS REFRAKSI PEDAGANG DI PERUMAHAN ALEKTRO WILAYAH PENJARINGAN JAKARTA UTARA - Urip Yusuf Suroso; Nisa Zakiati Umami; Zakaria Efendi (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
This study aims to determine how much the refraction status of traders in Alektro Penjaringan housing, North Jakarta. The research method used is quantitative with a descriptive approach, by conducting a subjective examination the researcher can find out the results of the patient being examined. The sample of this study used a saturated sampling technique, the traders in the Alektro Penjaringan housing estate, North Jakarta, taking data through observation, interviews and documentation. From the results of this study, it can be concluded that the refractive status that has been checked is 50% for emmetropia and 50% for ametropia. Researchers suggest educating every refractive examination to patients so that they do not experience advanced diseases such as cataracts